Metadiscourse and persuasion in expert-written online product reviews - Thanusha Karunakaran; Ang Leng Hong (Penerbit Universiti Kebangsaan Malaysia, 2025)
As online shopping becomes more widespread, consumers often rely on expert reviews to sift through countless product options and make smart purchasing decisions. Expert-written reviews, particularly those from reputable sources like Wirecutter, are viewed as more authoritative and trustworthy compared to user-generated reviews, making them a significant genre for analysis. This corpus-based study investigates the use of metadiscourse in expert-written online product reviews from The New York Times’ Wirecutter, focusing on how reviewers construct persuasive appeals through credibility (ethos), emotion (pathos), and rational (logos). Employing Hyland’s (2005a) Interpersonal Model of Metadiscourse, the analysis examines interactive markers (transitions, code glosses, endophoric markers, evidentials, frame markers) and interactional markers (self-mentions, attitude markers, hedges, boosters, engagement markers). The findings reveal a predominance of interactional metadiscourse, with self-mentions occurring most frequently, followed by engagement markers, attitude markers, hedges, and boosters. Among interactive markers, transitions were most common, followed by code glosses, evidentials, frame markers, and endophoric markers. This distribution highlights the dual focus of expert reviewers: establishing a credible authorial presence through self-mentions and ensuring coherence through transitions. The strategic use of self-mentions not only enhances credibility (ethos) but also fosters a sense of connection with readers, projecting the reviewers as authoritative yet relatable voices. Transitions aid in comparing products and structuring evaluations, ensuring clarity and rational appeal (logos). These findings shed light on the rhetorical strategies in expert reviews, contributing to linguistic and metadiscourse analysis. This study also offers practical guidance for crafting persuasive digital content, highlighting how metadiscourse supports effective persuasion.